Association of Insulin Resistance with Dyslipidemia in Gestational Diabetes Mellitus - Hasina, Hafsa; Islam, Md Hafizul; Haque, Mahmudul; Karim, Razaul; Akter, Shammi; Salma, Ummey (Journal of Chittagong Medical College Teachers’ Association, 2022)
Background: Gestational Diabetes Mellitus is the most common metabolic condition during pregnancy. Insulin resistance is a known risk factor for development of GDM. Women with Gestational Diabetes Mellitus are at increased risk for developing dyslipidemia. The aim of this study was to evaluate the occurrence of Dyslipidemia among women with GDM. Materials and methods: This cross-sectional comparative study was conducted in Obstetrics and Gynecology Department, Chittagong Medical College Hospital. 100 patients were taken by non-probability convenience sampling where 70 women with GDM were taken as cases and 30 normal pregnant women as controls. Results: GDM cases presented significantly higher mean HOMA-IR values and increased serum TC, TG, LDL-C and decreased HDL than those of controls. So from this point of view GDM cases had both insulin resistance and dyslipidemia. GDM patients with Insulin resistance had significantly higher Triglyceride level and decreased serum HDL-C level when compared to non-insulin resistance state of the same. This study revealed significant association of insulin resistance with dyslipidemia (Increased TG and decreased HDL-C, p<0.01) in GDM. Conclusion: Insulin resistance was significantly associated with dyslipidemia in GDM. Soestimation of fasting lipid profile and fasting insulin in women with GDM may provide baseline information in course of planning and management of GDM patients. JCMCTA 2022 ; 33 (1) : 40-45